Visual evoked potentials (VEP) and visual acuity improvement after cytidine 52 -diphosphocholine (CDP-Choline) therapy in amblyopic patient - Mendonça,Regina Halfeld Furtado de (2012)
Citicoline may be used in many neurological disorders. Combined treatment of citicoline with patching in amblyopia has previously been researched. The purpose of this paper is to illustrate the effect of citicoline in non-patching amblyopic patient. A 11-year-old amblyopic boy underwent complete ophthalmological examinations, including VEP with flash and pattern stimulus. Two averages of 100 sweep were performed for flash stimulus. Pattern reversal stimulus obtained with high contrast was performed with 60', 30' and 15' checks stimuli. The VEP was repeated 90 days later after a therapy with citicoline and vitamin and the results compared with the responses of the previous recording session. The visual acuity (VA) was 0,7 in the RE and 1,0 in the LE. The VEP pattern amplitude was normal in both eyes. Delayed in latency was detected for all spatial frequency stimulus (SFS) in the RE. Delay in latency was detected only for high SFS in the LE. After the treatment, the VA was 1,0 in both eyes. The latency was normalized with low SFS on the RE and with high SFS on the LE. The flash VEP was normal before and after the therapy. In conclusion, the citicoline demonstrated that it was effective in the treatment of amblyopic eye without patching. The VA and the VEP latency improvement demonstrated that the citicoline enhance the transmission of the electric impulse from retina to visual cortex. Further research is required to understand the immediate and long-term effect of coline treatment in amblyopic patients.